Malignant solid tumor-related spontaneous intracerebral hemorrhage: a propensity score matching study - Shuolin Liang; Liuyu Liu; Bin Qin; Shengri Chen; Zhijian Liang (PeerJ)
Background Spontaneous intracerebral hemorrhage (sICH) is a severe event with high mortality. Recently, evidence has emerged suggesting that malignant solid tumors may increase the risk of sICH through unique cancer-related factors. However, the specific risk factors and clinical characteristics of sICH in patients with malignant solid tumor remain poorly understood. Objective This study aimed to investigate the clinical characteristics of and identify the risk factors associated with sICH in individuals with malignant solid tumors. Methods This retrospective study was carried out in patients with active malignant solid tumors and sICH at the First Affiliated Hospital of Guangxi Medical University between January 2010 and December 2020. Patients were separated into control and malignant solid tumor-related spontaneous intracerebral hemorrhage (MST-sICH) groups. The control group consisted of patients presenting with malignant solid tumors alone who were matched to the MST-sICH group using a 1:1 propensity score matching (PSM) approach. Patient clinical data, laboratory findings, and imaging results were collected. Univariate analysis was carried out to determine the risk factors associated with MST-sICH. In addition, a receiver operator characteristic analysis was performed to identify potential predictors for poor prognosis. Results Decreased hemoglobin (HGB) levels, together with increased lymphocyte counts (LYCs), and an increased neutrophil-to-lymphocyte ratio (NLR) were found in the MST-sICH group compared to the control group. The results of the multivariate logistic regression analysis indicated a HGB levels (OR: 0.959, 95% CI [0.928–0.992]), an increased in LYCs (OR: 0.095, 95% CI [0.023–0.392]). Furthermore, there was an increased in NLR levels (OR: 2.137, 95% CI [1.427–3.200]). In the receiver operating characteristic (ROC) curve analysis, the area under the curve (AUC) with HGB, LYCs, and NLR as joint predictors was 0.955 (95% CI [0.901–1.000]), with a sensitivity of 100%, a specificity of 82.6%, and a Youden Index of 0.826. Conclusion Decreased HGB levels, elevated LYCs, and a higher NLR were identified as independent risk factors for sICH in patients with active solid malignancies. These markers could assist clinicians in stratifying high-risk patients, facilitating closer monitoring and informing targeted preventive strategies to mitigate the incidence of sICH in this at-risk population.